Tibialis Posterior Tenosynovitis and Associated Pes Plano Valgus in Rheumatoid Arthritis: Electromyography, Multisegment Foot Kinematics, and Ultrasound Features. Issue 4 (28th March 2013) - Barn, Ruth; Turner, Deborah E.; Rafferty, Daniel; Sturrock, Roger D.; Woodburn, James
Abstract Objective To compare electromyographic (EMG), kinematic, kinetic, and ultrasound (US) features of pes plano valgus associated with US‐confirmed tibialis posterior (TP) tenosynovitis in rheumatoid arthritis (RA) and healthy control subjects. Methods In this cross‐sectional study, patients with RA and US‐confirmed tenosynovitis of TP underwent gait analysis, including 3‐dimensional kinematics, kinetics, and intramuscular EMG of TP, and findings were compared with a group of healthy individuals. The RA group also underwent B mode and power Doppler US scanning of the TP tendon to assess and score levels of pathology. Results Ten patients with RA, median (range) disease duration of 3 years (1–18 years), and 5 control subjects were recruited. Compared to control subjects, the RA patients walked slower and presented with moderate levels of foot‐related disability. The mean ± SD Disease Activity Score in 28 joints was 4.6 ± 1.6. Increased magnitude of TP activity was recorded in the RA group compared to controls in the contact period of stance (P = 0.007), in conjunction with reduced ankle joint power (P = 0.005), reduced navicular height in the medial arch (P = 0.023), and increased forefoot dorsiflexion (P = 0.027). TP tendon thickening, fluid, and power Doppler signal were observed in the majority of patients. Conclusion This study has demonstrated, for the first time, increased TP EMG activity in the presence of US‐confirmed TP tenosynovitis in RA. Altered muscle function occurred in conjunction with suboptimal mechanics, moderate levels of tendon pathology, and active disease. Targeted therapy may be warranted to reduce inflammation and mechanically off‐load diseased tendon states.